Temporal patterns of daily occupations and personal projects relevant for older persons’ subjective health : a health promotive perspective - Björklund, Cecilia (Luleå tekniska universitet, Hälsa och rehabilitering, 2015)
Engagement in daily occupations has been shown to positively influence subjective health of older persons, but there is little knowledge of how such daily occupations should be temporally structured. This thesis is guided by two concepts to explore the temporal structure of daily occupations. Firstly, the concept temporal patterns of daily occupations are used to focus internal relationships and temporal order of daily occupations during 24-hour sequences. Secondly, the concept personal projects are used to focus sets of intentionally performed occupations structured to reach short- or long-term goals of a year. The overall aim of this thesis was to develop knowledge and understanding of temporal patterns of daily occupations and personal projects relevant for older persons’ health and well-being. This thesis includes four studies, according to a multi method sequential design. Participants in all four studies were recruited from retirement organizations in two municipalities in northern Sweden and all of them are living in their private urban or rural homes. For Study I and II, data of daily occupations and of health and well-being were collected from 151 older adults using open time-diaries completed for one week and two health questionnaires. A time-geographic method was used to analyze data from the time-diaries and descriptive and analytic statistics are applied for further analysis including the additional data from the two health questionnaires. The aim of Study I was to expand the knowledge regarding temporal patterns of daily occupations and to explore and describe older Swedish adults´ daily occupations from such a temporal pattern and time-use perspective. In Study I the temporal pattern of daily occupations of older persons was identified as real time-use and added time-use during 24-hour sequences. The pattern of real time-use showed i)a daily routine of six intervals ii) characteristic profiles illustrating number of participants in categorized occupations and iii) a pattern of merged categories of ...